The Politics of Representation: Arundhati Roy’s Re-framing of Media Narratives in The Ministry of Utmost Happiness (Spectrum, 2025)
In the current global scenario, media discourse has incontestably become one of the most powerful means of constructing the narratives which influence public response to the events occurring in the modern world. When the issue of media power is examined within the overarching paradigm of international media representation of events occurring in countries with a long-standing history of colonization, it becomes clear that earlier Orientalist attitudes are still potent in representing certain populations as inferior to and of lesser value than their Western counterparts. This essay will examine Arundahati Roy’s portrayal of media discourse in The Ministry of Utmost Happiness (2017) in the light of Edward Said’s ideas of Orientalism and Judith Butler’s notions of the frames of recognition used in media discourse to show that certain lives are considered more valuable and grievable than others. This essay will also demonstrate how media representation can be placed within the framework of global capitalism with images and stories being circulated according to market demands of global media consumption. Maintaining that Roy’s attitude to media narratives in her novel is ambivalent and complex, this essay will argue that her representation of these media narratives within the larger frame of the novel is a subversive act that makes transparent the assumptions underlying media discourse and power. Spectrum, Volume 18, June 2023: 10-21